The transition of smooth muscle cells from a contractile to a migratory, phagocytic phenotype: direct demonstration of phenotypic modulation. (13th August 2016) - Sandison, Mairi E.; Dempster, John; McCarron, John G.
Abstract : Key points: Smooth muscle cell (SMC) phenotypic conversion from a contractile to a migratory phenotype is proposed to underlie cardiovascular disease but its contribution to vascular remodelling and even its existence have recently been questioned. Tracking the fate of individual SMCs is difficult as no specific markers of migratory SMCs exist. This study used a novel, prolonged time‐lapse imaging approach to continuously track the behaviour of unambiguously identified, fully differentiated SMCs. In response to serum, highly‐elongated, contractile SMCs initially rounded up, before spreading and migrating and these migratory cells displayed clear phagocytic activity. This study provides a direct demonstration of the transition of fully contractile SMCs to a non‐contractile, migratory phenotype with phagocytic capacity that may act as a macrophage‐like cell. Abstract: Atherosclerotic plaques are populated with smooth muscle cells (SMCs) and macrophages. SMCs are thought to accumulate in plaques because fully differentiated, contractile SMCs reprogramme into a 'synthetic' migratory phenotype, so‐called phenotypic modulation, whilst plaque macrophages are thought to derive from blood‐borne myeloid cells. Recently, these views have been challenged, with reports that SMC phenotypic modulation may not occur during vascular remodelling and that plaque macrophages may not be of haematopoietic origin. Following the fate of SMCs is complicated by the lack of specific markers for the migratory phenotype and direct demonstrations of phenotypic modulation are lacking. Therefore, we employed long‐term, high‐resolution, time‐lapse microscopy to track the fate of unambiguously identified, fully‐differentiated, contractile SMCs in response to the growth factors present in serum. Phenotypic modulation was clearly observed. The highly elongated, contractile SMCs initially rounded up, for 1–3 days, before spreading outwards. Once spread, the SMCs became motile and displayed dynamic cell‐cell communication behaviours. Significantly, they also displayed clear evidence of phagocytic activity. This macrophage‐like behaviour was confirmed by their internalisation of 1 μm fluorescent latex beads. However, migratory SMCs did not uptake acetylated low‐density lipoprotein or express the classic macrophage marker CD68. These results directly demonstrate that SMCs may rapidly undergo phenotypic modulation and develop phagocytic capabilities. Resident SMCs may provide a potential source of macrophages in vascular remodelling. Key points: Smooth muscle cell (SMC) phenotypic conversion from a contractile to a migratory phenotype is proposed to underlie cardiovascular disease but its contribution to vascular remodelling and even its existence have recently been questioned. Tracking the fate of individual SMCs is difficult as no specific markers of migratory SMCs exist. This study used a novel, prolonged time‐lapse imaging approach to continuously track the behaviour of unambiguously identified, fully differentiated SMCs. In response to serum, highly‐elongated, contractile SMCs initially rounded up, before spreading and migrating and these migratory cells displayed clear phagocytic activity. This study provides a direct demonstration of the transition of fully contractile SMCs to a non‐contractile, migratory phenotype with phagocytic capacity that may act as a macrophage‐like cell.